Determination of chromium, mercury, selenium and zinc in marine fish species of Malaysia - Nazaratul Ashifa, Abdullah Salim; Wee, Boon Siong; Ezwiza, Sanuri; Mohd Suhaimi, Hamzah (2013)
Concentrations of chromium, mercury, selenium and zinc were determined in eight commonly edible marine fish species; mackerel, red snapper, thread fin, tuna, hard tail scads, val, doubled spotted queen fish and shark. This study was based on market basket method were those species were collected from two locations of Kuala Selangor and Kuala Terengganu. All elements were measured using instrumental neutron activation analysis (INAA) technique. The accuracy and precision analysis were checked by analyzing ...